A Mutation of the Prdm9 Mouse Hybrid Sterility Gene Carried by a Transgene - Mihola, O; Trachtulec, Z (Folia biologica, 2017)
PRDM9 is a protein with histone-3-methyltransferase activity, which specifies the sites of meiotic recombination in mammals. Deficiency of the Prdm9 gene in the laboratory mouse results in complete arrest of the meiotic prophase of both sexes. Moreover, the combination of certain PRDM9 alleles from different mouse subspecies causes hybrid sterility, e.g., the male-specific meiotic arrest found in the (PWD/Ph × C57BL/6J)F1 animals. The fertility of all these mice can be rescued using a Prdm9-containing transgene. Here we characterized a transgene made from the clone RP24-346I22 that was expected to encompass the entire Prdm9 gene. Both (PWD/Ph × C57BL/6J)F1 intersubspecific hybrid males and Prdm9-deficient laboratory mice of both sexes carrying this transgene remained sterile, suggesting that Prdm9 inactivation occurred in the Tg(RP24-346I22) transgenics. Indeed, comparative qRT-PCR analysis of testicular RNAs from transgene-positive versus negative animals revealed similar expression levels of Prdm9 mRNAs from the exons encoding the C-terminal part of the protein but elevated expression from the regions coding for the N-terminus of PRDM9, indicating that the transgenic carries a new null Prdm9 allele. Two naturally occurring alternative Prdm9 mRNA isoforms were overexpressed in Tg(RP24-346I22), one formed via splicing to a 3'-terminal exon consisting of short interspersed element B2 and one isoform including an alternative internal exon of 28 base pairs. However, the overexpression of these alternative transcripts was apparently insufficient for Prdm9 function or for increasing the fertility of the hybrid males.
Keywords: hybridizace genetická; mutace; Animals; histonlysin-N-methyltransferasa; Female; Transgenes; ženské pohlaví; infertilita; messenger RNA; Mutation; transgeny; Infertility; Hybridization, Genetic; křížení genetické; RNA, Messenger; regulace genové exprese; Histone-Lysine N-Methyltransferase; Male; Crosses, Genetic; Gene Expression Regulation; zvířata; mužské pohlaví; Mice, Inbred C57BL; myši inbrední C57BL